Militairen beveiligen kar met meel op Leidsche Plein. Uit: archief F. Domela Nieuwenhuis, VI a 1B, no.44. Originele foto BG A61/178
Militairen beveiligen kar met meel op Leidsche Plein. Uit: archief F. Domela Nieuwenhuis, VI a 1B, no.44. Originele foto BG A61/178.